Wide pressure range condensation modeling on pure steam/steam-air mixture inside vertical tube. (August 2018) - Chung, Young-Jong; Kim, Hyungjun; Kim, Ho-Sik; Kim, Soo-Hyung; Bae, Kyoo-Hwan
Highlights: The realistic condensation correlations with pure steam or a steam-air mixture are proposed. The correlations predict the experimental results within 25% for a wide pressure range. The overall condensation heat transfer coefficient decreases as the system pressure increases. Abstract: The elimination of active systems and their replacement with passive systems are emphasized to improve a system reliability in advanced nuclear power plants such as SMART. For accident situations, a condensate heat exchanger having vertical tubes is an ultimate heat sink to remove residual heat generated in the core. To adequately analyze the system behaviors, a realistic condensation model with pure steam or a steam-air mixture in the condensate heat exchanger is important for the various thermal hydraulic conditions. Improved correlations are proposed to analyze the thermal hydraulic behaviors for wide pressure conditions of up to 6 MPa. For a validation of the condensation heat transfer for the condensate heat exchanger tube side, simulations of the UCB (University of California at Berkeley) and POSTECH (Pohang University of Science and Technology) condensation experiment are carried out, and the results are compared with the experimental data. For pure steam conditions, the correlations predict well or under-predict slightly the UCB experimental results and predict the POSTECH experimental results within 25%. The improved correlation predicts that the condensation heat transfer coefficient decreases as the system pressure increases as shown the POSTECH experiment.